1989
DOI: 10.1021/bi00442a016
|View full text |Cite
|
Sign up to set email alerts
|

Histone subunit interactions as investigated by high pressure

Abstract: High-pressure fluorescence polarization was used to investigate subunit interactions of the histone H2A-H2B dimer and the H3/H4 tetramer isolated from calf thymus (CT) and chicken erythrocyte (CE) chromatin. The proteins were individually labeled with the fluorescent probe 5-(dimethylamino)-naphthalene-1-sulfonate (dansyl or DNS), and the fluorescence polarization was measured as a function of pressure. The long fluorescence lifetime of the probe allows for the observation of global rotations of the protein, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…5), which revealed a decrease in the proportion of tetramers and an increase in monomers after pressurization. This is in line with previous studies of pressure effects on a number of tetrameric enzymes that showed dissociation into monomers [36–44]. However, those studies showed reversible tetramer dissociation, whereas we have found that under nonreducing conditions pyruvate kinase was irreversibly dissociated and inactivated by pressure (see below).…”
Section: Discussionsupporting
confidence: 93%
“…5), which revealed a decrease in the proportion of tetramers and an increase in monomers after pressurization. This is in line with previous studies of pressure effects on a number of tetrameric enzymes that showed dissociation into monomers [36–44]. However, those studies showed reversible tetramer dissociation, whereas we have found that under nonreducing conditions pyruvate kinase was irreversibly dissociated and inactivated by pressure (see below).…”
Section: Discussionsupporting
confidence: 93%
“…Reported in vitro K d values for chromatin binding proteins span several orders of magnitude 29, 30, 32–45 (Table 1). The Polycomb proteins are an interesting example.…”
Section: How Strong? In Vitro Studies Reveal Very Different Binding Amentioning
confidence: 99%
“…On the other hand, binding of the operator DNA sequence destabilizes the tetramer considerably. Dissociation constants for histone octamers, tetramers and dimers have been determined by using fluorescence polarization under high pressure (Scarlata et al, 1989).…”
Section: Dna-binding Proteinsmentioning
confidence: 99%